Neutrophil extracellular traps and cannabinoids: potential in cancer metastasis - Krauze, Izabela; Greb-Markiewicz, Beata; Kłopot, Anna; Maciejewska, Kamila; Bryk, Michał; Krzystek-Korpacka, Małgorzata (Frontiers in Oncology, 2025)
Cancer is the second leading cause of global mortality after cardiovascular diseases, with breast, lung, colon, and prostate cancers being the most common. WHO projects around 30 million new cancer cases worldwide by 2045, with breast cancer being the most common in women and lung cancer in men. Metastasis is responsible for nearly 90% of cancer-related deaths. Breast and lung cancers tend to metastasize to the bones, lymph nodes, lungs, liver, and brain. Lungs remains one of the most common organs to which various forms of cancer metastasize. An important factor in metastasis is NETosis – it can initially help to eliminate cancer cells, but it can also promote metastasis. Phytocannabinoids, compounds derived from Cannabis sativa, and the endocannabinoid system (ECS) offer promising therapeutic potential to inhibit NETosis and consequently cancer development and metastasis. Although the precise effects of phytocannabinoids on neutrophil functions and NETosis are not fully understood and require further research in the context of cancer, preliminary studies suggest their potential to inhibit NET release in various disease models. This review consolidates current knowledge and provides new insights into how phytocannabinoids and the ECS may serve as effective therapeutic tools to limit cancer metastasis.